FRI0388 Patterns of compliance to allopurinol in "real life population" – is everything crystal clear?. (23rd January 2014) - Zandman-Goddard, G.; Shamrayevsky, N.; Chodick, G.; Agmon-Levin, N.; Shalev, V.; Amital, H.
Abstract : Background: Gout is a chronic crystal induced arthritis caused by the precipitation of monosodium urate crystals in the joints leading to inflammation and pain. Therapy includes non-steroidal anti-inflammatory drugs, steroids, allopurinol, and colchicine. Therapy with allopurinol is utilized to prevent further attacks and to maintain a normal uric acid level. Objectives: The aim of this study was to assess patterns that influence compliance to allopurinol therapy in the Israeli population utilizing the Maccabi Health Services database. Methods: Patients with the diagnosis of gout treated with allopurinol, were identified over a 7 year period (2002-2008) via the Maccabi Health Services database. They were assessed for the degree of compliance (compliance, adherence, and persistence) by the proportion of days covered (PDC) by allopurinol prescriptions provided by the family physician. Demographics including age, sex, marital and socioeconomic status, smoking history, and concomitant chronic diseases (hypertension, diabetes, cardiovascular disease) were assessed. Statistical methods were multi and univariate analysis and logistic regression. Results: 7644 patients were identified, predominantly men (72%). During 2008, 2.6 new cases per 1000 patient years were found. Only 1331 (17%) of patients were compliant to allopurinol therapy, 36% complied partially, and 47% complied poorly. The average time to discontinuation of therapy in men compared to women was 358 day and 379 days respectively. Compliance was associated with the number of doctor visits. There was a 4% statistically significant risk of non-compliance for every 1 mg/dl increase of uric acid levels. By univariate and multivariate analysis, women (45-65 years old) when compared to the older age group and to men were significantly more prone to be non-compliant. Non-married individuals and those of a low socioeconomic status were also more often non-compliant. Patients with increased body weight and concomitant illnesses were more compliant. Logistic regression (n-2471, 32% of the study sample) evaluated by doctor visits confirmed a 4.5 risk of non-compliance among 45-65 year old women. Compliance was achieved among those with chronic illnesses particularly cardiovascular disease. Conclusions: Women aged 45-65 years old are a particular increased risk for non-compliance with allopurinol therapy for chronic gout. Evaluation of compliance trends in this population can be beneficial to insure proper treatment outcomes. Disclosure of Interest: None Declared